Dynamic adjustment model of performance guarantee quota based on optimization decision of medium/long-term transactions of power selling companies - Jingbin Wu; Ke Meng (Energy Reports, 2023)
The existing mode of the fixed performance guarantee quota, which is susceptible to subjective determination, results in a lack of objectivity in the cost calculations of power selling companies, and has an impact on the calculation of their trading profits. Thus, it negatively impacts the stability of power market transactions as well as the operating enthusiasm of power selling company. Therefore, a dynamic adjustment strategy for performance guarantee quota is proposed, taking into account assessment criteria for the economic benefit of power selling companies, such as the degree of credit overdraft, the level of market share impact and national policies. Based on the fuzzy analytic hierarchy process (FAHP), the proposed dynamic adjustment model of the performance guarantee quota of power selling companies is established. To maximize the profit of power selling companies, the optimization decision of multiple types of transactions based on the proposed dynamic adjustment model of performance guarantee quota is carried out, such as decision-making of the medium/long-term transactions. Based on numerical simulations in MATLAB, the dynamic adjustment range of the performance guarantee quota is given. The suitability and effectiveness of the adjusted performance guarantee quota are verified by comparing and analyzing the differences, in the cost of power selling company in multiple scenarios.